Comparing predictions of long-term soil carbon dynamics under various cropping management systems using K-model and CENTURY - Li, Tao; Li, Xiaomei; Feng, Yongsheng (International Journal of Agricultural and Biological Engineering, 2012)
There is a strong demand for accurate estimates of long-term changes in soil organic carbon (SOC) with different agricultural practices under different soil and climate conditions. A process and analytic model, K-model, including a non-compartmental algorithm of soil carbon decomposition, was developed to simulate the changes of SOC under different cropping and soil management practices. This study evaluates the performance of K-model by comparing its predictions on SOC with measurements and predictions of CENTURY model, which is widely used for the similar purposes. Both K-model and CENTURY can predict the dynamics of SOC when site-specific soil and climate data are used to initialize simulations. Very similar annual carbon decomposition rates were simulated by the single carbon pool K-model and the 3-carbon pool CENTURY model. However, compared with experimental measurements of SOC, K-model produces relative smaller errors than CENTURY (<0.1 kg C m-2 vs. 0.08-0.48 kg C m-2, and within